2007
DOI: 10.1182/blood-2006-10-050260
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy augments the anticancer activity of the histone deacetylase inhibitor SAHA to overcome Bcr-Abl–mediated drug resistance

Abstract: Novel therapeutic strategies are needed to address the emerging problem of imatinib resistance. The histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) is being evaluated for imatinib-resistant chronic myelogenous leukemia (CML) and has multiple cellular effects, including the induction of autophagy and apoptosis. Considering that autophagy may promote cancer cell survival, we hypothesized that disrupting autophagy would augment the anticancer activity of SAHA. Here we report that drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
394
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(411 citation statements)
references
References 48 publications
15
394
1
1
Order By: Relevance
“…Several important anticancer agents, including arsenic trioxide, 5-FU, tamoxifen, imatinib, paclitaxel and cisplatin , has been shown to induce atutophagy in a few types of cancer cells (Bursch et al, 1996;Paglin et al, 2001;Carew et al, 2007;Shingu et al, 2009;Goussetis et al, 2010;Liu et al, 2011;Xi et al, 2011;Yang et al, 2011). In the present study, we have demonstrated that autophagy is also induced in glioblastoma cells during the course of GA treatment.…”
Section: Discussionsupporting
confidence: 64%
“…Several important anticancer agents, including arsenic trioxide, 5-FU, tamoxifen, imatinib, paclitaxel and cisplatin , has been shown to induce atutophagy in a few types of cancer cells (Bursch et al, 1996;Paglin et al, 2001;Carew et al, 2007;Shingu et al, 2009;Goussetis et al, 2010;Liu et al, 2011;Xi et al, 2011;Yang et al, 2011). In the present study, we have demonstrated that autophagy is also induced in glioblastoma cells during the course of GA treatment.…”
Section: Discussionsupporting
confidence: 64%
“…Yet another investigation has shown that inhibition of autophagy by chloroquine enhances the pro-apoptotic effects of the histone deacetylase suberoylanide hydroxamic acid in primary chronic myelogenous leukaemia cells from patients clinically refractory to imatinib. 43 Interestingly, the pro-death synergism between these two drugs was associated with disruption of lysosomal membrane integrity and cathepsin D-mediated degradation of thioredoxin, a key regulator of cellular redox status. 43 These findings underscore the complexity of the role(s) of autophagy in anticancer drug response, which likely depend on the actual level of autophagy in the cell and the cytotoxic mechanism of the therapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…43 Interestingly, the pro-death synergism between these two drugs was associated with disruption of lysosomal membrane integrity and cathepsin D-mediated degradation of thioredoxin, a key regulator of cellular redox status. 43 These findings underscore the complexity of the role(s) of autophagy in anticancer drug response, which likely depend on the actual level of autophagy in the cell and the cytotoxic mechanism of the therapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inhibition of autophagy can sensitize tumor cells to a wide selection of drugs. 32,33 In essence, autophagy-dependent mechanisms that contribute to the maintenance of cellular homeostasis could indirectly postpone the onset of apoptosis, for example, by recycling or eliminating damaged organelles and cytotoxic protein aggregates. 34,35 As the parent withaferin A strongly induces endogenous PAWR for prostate cancer cell sensitization to apoptosis, 10 we therefore sought to investigate the role of the more potent derivative 3-AWA in mediating PAWR activation in the autophagy-apoptosis switching cascade in CaP cells.…”
Section: The 3-awa-induced Autophagy To Apoptosis Switching Is Mediatmentioning
confidence: 99%